2020
DOI: 10.1002/jor.24935
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utilization of species‐specific immunoassays for identification of Staphylococcus aureus and Streptococcus agalactiae in orthopedic infections

Abstract: Staphylococcus aureus and Streptococcus agalactiae (Group B streptococcus, GBS) are common causes of deep musculoskeletal infections (MSKI) and result in significant patient morbidity and cost to the healthcare system. One of the major challenges with MSKI is the lack of faithful diagnostics to correctly identify the primary pathogen, as standard culture-based assays are prone to false positives in the case of polymicrobial infections, and false negatives due to limitations in sample acquisition and antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The key characteristics of these bacteria species and their related diseases are listed below in Table 3. [86,87] Colonizes the genital tract of some women, causing vertical transmission Neonatal sepsis, meningitis, pneumonia S. pneumoniae [88,89] Respiratory pathogen, some strains have antibiotic resistance Pneumonia, Bacteremia, Meningitis, Otitis Media, Sinusitis K. pneumoniae [90,91] Gram-negative bacterium, respiratory pathogen, urinary tract pathogen, some strains have antibiotic resistance…”
Section: Antibacterial Efficiency Testsmentioning
confidence: 99%
“…The key characteristics of these bacteria species and their related diseases are listed below in Table 3. [86,87] Colonizes the genital tract of some women, causing vertical transmission Neonatal sepsis, meningitis, pneumonia S. pneumoniae [88,89] Respiratory pathogen, some strains have antibiotic resistance Pneumonia, Bacteremia, Meningitis, Otitis Media, Sinusitis K. pneumoniae [90,91] Gram-negative bacterium, respiratory pathogen, urinary tract pathogen, some strains have antibiotic resistance…”
Section: Antibacterial Efficiency Testsmentioning
confidence: 99%
“…Further studies have shown that S. aureus also infects living osteocytes and forms small colony variants in this niche in vitro; moreover, infection of osteocytes has also been shown in human patients (Yang et al, 2018). As each osteocyte has approximately 40-50 canaliculi (Beno et al, 2006;Tiede-Lewis et al, 2017), these cells may effectively serve as OLCN "hubs" for continued bacterial invasion to neighbouring and distant osteocytes within bone tissue and may be a key factor in infection persistence.…”
Section: Invasion Of Bone Canaliculi By S Aureusmentioning
confidence: 99%
“…Decreased T cell and B cell activation is associated with reduced production of S. aureus-specific IgG (Farnsworth et al, 2018a;Farnsworth et al, 2015). Immuneimpairing hyperinflammation in the obese/T2D host is also linked to other complications of this disease, including liver dysfunction, islet inflammation and gut dysbiosis, which appear to be primarily mediated by obesity (Belkaid and Hand, 2014;Lumeng and Saltiel, 2011;Thingholm et al, 2019). Thus, targeting the causes of inflammation in obese/T2D patients, such as the well-recognised gut dysbiosis, opens promising new avenues for decreasing susceptibility to the more severe implant-associated osteomyelitis and other complications in this disease population.…”
Section: Fracture Stability and Infectionmentioning
confidence: 99%
See 2 more Smart Citations